Pandemic Impact on Lithuania‘s tour operators - Gruodė, Greta; Achonen, Irena; Variakojiene, Jolita (Turystyka i Rozwój Regionalny, 2021)
Lithuania tourism market was one of the fastest growing in Europe in 2019. All around the globe 2019 was a year of records for travelling, but 2020 changed everything. At the moment COVID-19 pandemic is one of the most important and relevant factor for influencing Tourism sector. It changed the way we‘re working, travelling, communicating, it had a huge negative effect on specific sectors there people meet, spend time together. Tour operators are one of the most affected in the business world because of economic and political reasons: for most of the year countries have travelling restrictions, borders closed, obligation for testing before and after travelling and in general consumer behaviour is changed due to the safety reasons. This paper aims to analyze the impact of pandemic to Lithuania‘s Tour operators as well as present the overview of previous year numbers of tourism. Qantative research – a survey was conducted with the most active Lithuania‘s tour operators, working with inbound, outbound and domestic tourism in order to find out their opinion of previous year and currently happening change. Results are presented in a paper. Topic is extremely relevant these days and the paper reveal the current situation in Lithuania‘s travel market.